PERBANDINGAN VARIASI DURASI INJEKSI DAN WAKTU PENGAPIAN TERHADAP PERFORMA DAYA MESIN MOTOR 4 LANGKAH MENGGUNAKAN BAHAN BAKAR PERTAMAX - Darwin Rio Budi Syaka; Imam Mahir; Guruh Muharrom Muslim (Universitas Negeri Jakarta, 2023)
The main component of the injection system is the electronic control unit (ECU) functions to optimize the performance of the vehicle engine. The ECU has the functions of injection duration and ignition time as an injector and ignition controller. The purpose of the study analyzed the comparison and differences in variations in the regulation of injection duration and ignition time of injection motor engines against the power output of the engine using pertamax fuel by experimental methods. There are comparisons and differences in power and torque in each variation of the programmable ECU and standard ECU settings. The highest average power and torque results at the standard ECU setting compared to the programmable ECU setting have lower average power and torque. Due to the different injection duration and ignition time of each setting, the power and torque generated by the motorcycle engine can be higher or lower per variation of the Programmable ECU setting. In addition to the difference in power output and engine torque, it also has differences in SFC values and the average Thermis Efficiency produced varies by variation of the programmable ECU settings.